A study to assess the performance of an "X-ray powder diffraction with Rietveld" approach for measuring the crystalline and amorphous components of inhalable dust collected on aerosol sampling filters. Issue 3 (September 2019) - Stacey, P.
Abstract : This work was undertaken in preparation for a survey to assess the exposure of carpenters to hazardous dust working in construction. Inhalable dust, in this industry, was expected to contain both crystalline mineral and amorphous phases (wood dust). The Rietveld method was applied to provide a simultaneous multicomponent analysis. To assess its performance, mixtures of aerosolised calcite, gypsum, quartz, kaolinite, and wood dust were collected onto quartz fibre filters ( n = 41) using the Button inhalable sampler. Results obtained using Rietveld were compared with loaded mass and those from external standard calibrations. The measured content of a component in 14 samples was used as an internal standard by Rietveld to determine amorphous content (wood). The performance of the Rietveld and external standard methods was similar. The 95% confidence interval for the absolute differences between the two methods was 15%. Only one relative difference of more than 15% had a mass loading >0.5 mg. An approach for assessing the limits of detection with relative intensity ratios was applied and gave comparable values with the usual method using calibration coefficients from the external standard method. Rietveld is therefore a potentially useful multicomponent method for the measurement of dust aerosol to help better understand workers' exposures.